2008
DOI: 10.1200/jco.2006.10.1022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Tamoxifen Discontinuation Among Older Women With Estrogen Receptor–Positive Breast Cancer

Abstract: Attention to nonadherence among older women at risk of discontinuation, particularly those receiving BCS without radiotherapy, might improve breast cancer outcomes for these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
255
5
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(274 citation statements)
references
References 31 publications
12
255
5
2
Order By: Relevance
“…Although several studies performed in clinical practise settings (Waterhouse et al, 1993;Demissie et al, 2001;Silliman et al, 2002;Partridge et al, 2003Partridge et al, , 2008Fink et al, 2004;Grunfeld et al, 2005;Atkins and Fallowfield, 2006;Lash et al, 2006;Barron et al, 2007;Owusu et al, 2008) and clinical trials (Fisher et al, 1989;Coombes et al, 2004;Coates et al, 2007;Forbes et al, 2008) have addressed non-adherence to endocrine therapy for breast cancer, the conclusions that can be drawn from the currently available evidence are significantly limited. The reported rates of nonadherent patients in adjuvant endocrine therapy of breast cancer range considerably from 15 to 50%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although several studies performed in clinical practise settings (Waterhouse et al, 1993;Demissie et al, 2001;Silliman et al, 2002;Partridge et al, 2003Partridge et al, , 2008Fink et al, 2004;Grunfeld et al, 2005;Atkins and Fallowfield, 2006;Lash et al, 2006;Barron et al, 2007;Owusu et al, 2008) and clinical trials (Fisher et al, 1989;Coombes et al, 2004;Coates et al, 2007;Forbes et al, 2008) have addressed non-adherence to endocrine therapy for breast cancer, the conclusions that can be drawn from the currently available evidence are significantly limited. The reported rates of nonadherent patients in adjuvant endocrine therapy of breast cancer range considerably from 15 to 50%.…”
Section: Discussionmentioning
confidence: 94%
“…Patient refusal to initiate the recommended antihormonal medication and non-adherence to therapy (defined as a composite of compliance and persistence: the patient started therapy, but discontinued the planned treatment) are important, but are not the only contributors. Both factors were evaluated in several studies, in clinical trials (Fisher et al, 1989;Coombes et al, 2004;Coates et al, 2007;Forbes et al, 2008) and in clinical practise settings (Waterhouse et al, 1993;Demissie et al, 2001;Silliman et al, 2002;Partridge et al, 2003Partridge et al, , 2008Fink et al, 2004;Grunfeld et al, 2005;Atkins and Fallowfield, 2006;Lash et al, 2006;Barron et al, 2007;Owusu et al, 2008). These studies, however, evaluated only selected populations and failed to describe all the possible situations that determine compliance and adherence to therapy in everyday clinical settings.…”
mentioning
confidence: 99%
“…By year 4 or 5 of treatment, the full adherence rate drops to 50% (14,16). Similarly, nonpersistence with adjuvant tamoxifen is about 20% to 30% at year 1 or 2 (15,17,18) and climbs to as high as 49% before the completion of 5 years (15,16,19). Available data on the association between adherence to adjuvant tamoxifen therapy and breast cancer outcomes have suggested that poor tamoxifen adherence contributes to therapeutic failure with an increased risk for poor outcomes.…”
Section: Early Disease/adjuvant Therapymentioning
confidence: 99%
“…Severe adverse events and side effects, or concerns about their development, are certainly likely to cause women to discontinue the treatment (9, 10). There is some evidence that ethnicity, demographic factors, including socioeconomic status, education level, and age, especially extremes of age under 40-45 and over 75-85, have also been linked to lower adherence (14,16,19,(22)(23)(24) (Table 1). Of the 2 pivotal adherence analyses in the adjuvant setting, Partridge and colleagues (14) found that age younger than 45 years or 85 years or older and nonwhite ancestry were the major predictors for poor (<80%) adherence to tamoxifen at 4 years in 2,378 adjuvant patients.…”
Section: Early Disease/adjuvant Therapymentioning
confidence: 99%
“…Elderly patients with comorbidity do not receive standard cancer therapy because aging often involves a decline in tumor aggressiveness and a corresponding decline in the effectiveness of treatment such as chemotherapy [34][35][36]. The chance of completing the course of treatment is also lower among these patients [37]. Large randomized trials usually exclude elderly patients with breast cancer, as well as people with comorbidities, thus there is an insufficient evidence for the treatment of such patients [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%